Bantuan Hukum Terhadap Korban Tindak Pidana Human Trafficking (Studi di Kabupaten Banyumas) - Kinantan, Anjeng (Universitas Pahlawan Tuanku Tambusai, 2024)
With the rise in organized human trafficking crimes, protecting victims has become increasingly difficult due to the cross-border nature of these crimes. It is vital to carry out structured and methodical research on victim protection, including the legal support provided by courts and legal aid agencies. This research aims to ease the burdens faced by economically disadvantaged communities and contribute to upholding social justice and legal protection. The focus is on evaluating and analyzing the implementation of legal aid for humman traafficking victims in banyumas. The inquiry relies on a qualitative analytical approach with a juridical-sociological perspective and a descriptive-analytical method. The data collection process includes interviews with primary and secondary sources and literature reviews, and are systematically organized. Findings indicate that legal aid for victims in Banyumas Regency complies with existing laws. However, issues such as insufficient funding and the lack of psychological services impact the effectiveness of this aid.